Artificial insemination system without estrous observation in suckled beef cows - Borges,Luiz Felipe Kruel (2009)
The aim was to develop a timed artificial insemination (TAI) system in suckled beef cows. Cows (n=227), 60-80 days postpartum, received estradiol benzoate (5mg) and a vaginal device containing 250µg of medroxyprogesterone acetate (MPA; day 0). On day six, cloprostenol (125µg) and eCG (400IU) were administrated and calves were weaned for 88h. The devices were removed on day seven (BioRep group) or on day eight (TAI group). All cows of TAI group and cows of BioRep group that did not exhibit standing estrus received GnRH (100µg) on day 9. In experiment I, the follicular growth was monitored daily by transrectal ultrasound exams, from day 6 to day 9. The average size of the dominant follicle on day nine was 11.1±0.99mm (BioRep, n=7) and 11.5±0.65mm (TAI, n=7) and all animals ovulated. In experiment II, the BioRep group cows (n=106) were observed for estrous behavior after withdrawal of the device, twice a day for 48h, and inseminated 12h after detection. In the TAI group (n=107), the devices were withdrawn on day eight and after 24h these cows and those from the BioRep group, which were not stand in estrus, received 100µg of GnRH and TAI 16h later. The pregnancy rates were 57.6% (BioRep) and 52.3% (TAI). In conclusion, an increase on MPA exposure time did not affect the follicular dynamics and pregnancy rates and allow TAI without estrous observation. Furthermore, the treatment for eight days provides an efficient TAI system in suckled beef cows.